Synthesis and antibacterial activity of some heterocyclic derivatives of sulfanilamide - B.B. Subudhi (Bulletin of the Chemical Society of Ethiopia, 2012)
Considering the promising antimicrobial potential of carbonic anhydrase inhibitors and heterocyclic compounds some heterocyclic derivatives of sulfanilamide (2a-e) were synthesized. The diazotisation of sulfanilamide followed by substitution with ethylacetoacetate and further condensation yielded compounds 2a-c. Schiff base of sulfanilamide with salicylaldehyde on reaction with thioglycollic acid and chloroacetyl chloride resulted in compound 2d-e. The susceptibility of Staphylococcus aureus, Enterococcus faecalis, Escherichia coli and Pseudomonas aeruginosa to the title compounds (300 μg/disc) was investigated and compared to that of nitrofurantoin (300 μg/disc) and ciprofloxacin (25 μg/disc). The title compounds showed good antimicrobial activity.DOI: http://dx.doi.org/10.4314/bcse.v26i3.15